Epidemiologic trends of cleft lip and/or palate in Switzerland - Joël Beyeler; Anic Lauener; Christos Katsaros; Giorgio C. La Scala; Martin Degen (BMC Oral Health)
Abstract Background Epidemiologic data on the number of cleft lip and/or palate (orofacial cleft (OFC)) births in Switzerland are currently sparse. However, this knowledge is essential for better understanding the etiologies underlying the various cleft phenotypes and providing expectant parents with the best possible healthcare planning and counseling. Methods This is the first descriptive study to report data on the prevalence of the various cleft types, their sex, and regional distributions in Switzerland. Data for the years 1998–2021 were obtained from the Swiss Federal Statistical Office. Due to the notable initial underreporting of cleft cases from 1998 to 2006, this period was omitted from the final analyses. Results Between 2007 and 2021, the prevalence of all Swiss OFC cases per 10,000 live births was 12.5, with a stable trend. Cleft lip was the least common anomaly. Except for cleft palate, which was more common in females, males were generally more affected by OFC than females. There was no discernible regional trend for any of the malformations, even though the prevalence differed throughout the seven Swiss regions. Conclusions This study presents the first descriptive epidemiologic profiles for OFCs in Switzerland and emphasizes the importance of nationwide OFC registries with an accurate and reliable reporting system for the benefit of current and future patients with clefts, their parents or caregivers, and society as a whole.